Diagnosing timber defects in traditional Malay house: a case study of Tok Abu Bakar Alang Ketak (TABAK) nature of building defects in Tok Abu Bakar Alang Ketak House (TABAK) / Haryati Mohd Isa ... [et al.] - Mohd Isa, Haryati; Baharuddin, Mohd Nurfaisal; Mohd Nor, Othman; Ab Rashid, Mohd Sabrizaa; Sedhu, Daljeet Singh; Abdul Manap, Muhammad Daniel; Dzulkifly, Najat Affendy (Universiti Teknologi MARA, Perak, 2021)
Timber traditional houses can bring a significant image of Malaysian built environment heritage. Indeed, it is one of the most valuable treasures that must be sustained for future global reference thus, the building owner and the professional must undertake the responsibility to ensure that these assets are in good condition and safe for its occupants. This paper aims to identify the nature of timber defects that occurred in Tok Abu Bakar Alang Ketak House. Two research objectives had been established (i) to identify the types of timber defects and (ii) to determine the causes of the occurrence of the defects. A mixed-method approach was adopted. The building inspection was carried out from the external to the internal of the building through a grid number from the building plan. All timber defects for each building element were recorded in the conditional survey form. The data were analysed using frequency analysis to measure the frequency of the defects occurring. The findings suggest that with a proper methodology in place, there is much that can be learned from studying the cause of the defect. It will provide some insights to the owner/caretaker in planning to repair for replacement work in order to sustain the house.